Miwok materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
Two items relating to Miwok languages have been identified in the C. F. Voegelin Papers. They are both in Subcollection II, and consist of some Miwok information in a folder labeled Eskimo-Aleutian in Series II. Research Notes, Subseries I. Eskimo-Aleutian; and a separate Miwok folder in Series II. Research Notes, Subseries VI. Penutian, including Mayan and Zoque. The latter includes some typewritten interlinear texts and notes based mainly on Lucy S. Freeland's work.